2013
DOI: 10.3892/etm.2013.1052
|View full text |Cite
|
Sign up to set email alerts
|

The urotensin II receptor antagonist, urantide, protects against atherosclerosis in rats

Abstract: The aim of this study was to explore the use of urantide as an antagonist of the urotensin II (UII) receptor, G protein-coupled receptor 14 (GPR14), to protect against atherosclerosis (AS) in rats. The AS rat model was induced by an intraperitoneal injection of vitamin D3 (VD3) into rats fed with a high-fat diet for four weeks. Urantide was then injected into the rats. Immunohistochemical staining, serum biochemical assay, reverse transcription-polymerase chain reaction (RT-PCR) and western blotting were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…HDL is assumed a key lipoprotein that helps lipid removal from macrophage foam cells in the arterial wall, and thus protects LDL oxidation. Several studies have been performed using albino Wistar rats as experimental atherosclerosis model, and they found it suitable and effective model to be used in condition of hypercholesterolemia and atherosclerosis [27,28]. In the present study, we have performed gas chromatography (GC) analysis of the ME and VO, fractionated from NS seed oil and identified their constituents by using two different mass spectrometry (MS) libraries.…”
Section: Introductionmentioning
confidence: 99%
“…HDL is assumed a key lipoprotein that helps lipid removal from macrophage foam cells in the arterial wall, and thus protects LDL oxidation. Several studies have been performed using albino Wistar rats as experimental atherosclerosis model, and they found it suitable and effective model to be used in condition of hypercholesterolemia and atherosclerosis [27,28]. In the present study, we have performed gas chromatography (GC) analysis of the ME and VO, fractionated from NS seed oil and identified their constituents by using two different mass spectrometry (MS) libraries.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] In particular, the latter provides an intriguing tool in the field of alternative pharmacological strategies, because negative modulation of the urotensinergic system can be useful in the treatment of various diseases such as atherosclerosis [16] and colon cancer. [17] Therefore, the discovery and availability of various ligands that can finely modulate the UT might be helpful in clarifying the role of hU-II as a multipurpose peptide in mammalian pathophysiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the urotensinergic system, composed of a class 1A G protein-coupled receptor (hUT), and two endogenous peptide ligands, urotensin II (UII; hUII = H-Glu-Thr-Pro-Asp-c[Cys-Phe-Trp-Lys-Tyr-Cys]-Val-OH) and urotensin II-related peptide (URP, H-Ala-c[Cys-Phe-Trp-Lys-Tyr-Cys]-Val-OH), continues to represent a promising contemporary target for the treatment of several pathologies (1,2). Notably, multiple studies in animal models have suggested that UT antagonists may represent potential therapeutic agents for treating atherosclerosis (3)(4)(5)(6), pulmonary arterial hypertension (7)(8)(9), metabolic syndrome (4), and heart failure (10)(11)(12). However, in spite of such promise, clinical studies of UT antagonist drug candidates have had limited success due to a lack of efficacy in humans (1,2,13,14).…”
Section: Introductionmentioning
confidence: 99%